2007
DOI: 10.1002/eat.20384
|View full text |Cite
|
Sign up to set email alerts
|

Satiety and test meal intake among women with binge eating disorder

Abstract: Individuals with BED consumed significantly more food and showed blunted changes in hunger and fullness during both the binge and nonbinge meals. These findings suggest that individuals with BED may have disturbances in satiety that in some ways resemble those described among individuals with bulimia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 22 publications
9
57
2
3
Order By: Relevance
“…These disturbances specifically may occur under stress and are not only restricted to binge-like situations, but are already effective during normal meals. The disturbance of the satiation process in obese BED patients has also been suggested by Sysko et al 8 Although not using a stressor, they were able to demonstrate that individuals with BED consume significantly more food than obese controls after being instructed to eat a normal meal. The process of eating appears to be characterized by a diminished increase in fullness, particularly during the latter portion of the meal.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These disturbances specifically may occur under stress and are not only restricted to binge-like situations, but are already effective during normal meals. The disturbance of the satiation process in obese BED patients has also been suggested by Sysko et al 8 Although not using a stressor, they were able to demonstrate that individuals with BED consume significantly more food than obese controls after being instructed to eat a normal meal. The process of eating appears to be characterized by a diminished increase in fullness, particularly during the latter portion of the meal.…”
Section: Discussionmentioning
confidence: 76%
“…A somewhat unexpected finding is the lack of a main effect of group (BED vs. non-BED) on total meal intake, because most studies have found that obese individuals with BED when compared with equally obese individuals without BED eat more in both binge and nonbinge conditions (for a review, see 5 further studies 6,8 ). However, there are studies who also did not find significant differences between these groups concerning the amount of food intake, 27,28 whereas in one of these studies there was no interview-based diagnosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Following instructions to binge, laboratory studies of persons meeting provisional criteria for BED suggest that these individuals eat significantly more kilocalories during a test meal in comparison to obese controls [14][15][16]41,44,45 and normal weight controls, 16,41,44,45 and this effect occurs regardless of negative mood state. 40 Such differences in binge episode intake did not reach statistical significance for other studies using self-report food diaries 36 or test-meal paradigms that manipulated the presentation amount of binge foods.…”
Section: Dsm-iv-tr Defined Attributes Of a Bingementioning
confidence: 94%
“…Additionally, a growing body of research has stressed the pervasive impact of shame (Duarte et al, 2014(Duarte et al, , 2015b and self-criticism (Gilbert, 2002;Goss and Allan, 2009;Goss and Gilbert, 2002) on binge eating and eating psychopathology, which goes beyond the overall negative affect. Another characteristic that seems to be an important feature of binge eating conceptualization is the dysregulation of satiety and hunger awareness (Sysko et al, 2007) as well as the reactivity to food-related cues (Sobik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%